HIV/AIDS and Nutrition: A Review of Current Evidence - KC, Tulza (Journal of Nursing Education of Nepal, 2023)
Human Immune Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) epidemic is increasingly  driven by and contributes to factors that also create malnutrition. Nutrition plays a critical role in  comprehensive care, support and treatment of HIV infected people. There are complex interactions  between nutrition and HIV/AIDS. HIV progressively weakens the immune system and leads to  malnutrition. Malnutrition worsens the effects of HIV and contributes to more rapid progression  to AIDS. The association of malnutrition, micronutrient deficiencies, weight loss and muscle  wasting with the increased morbidity and mortality is clearly present in patients living with HIV/  AIDS. The available evidence shows that nutritional education, counseling and supplementation  improve nutritional status among people with HIV/AIDS. Thus to conclude, nutrition should be fully  incorporated into care, support and treatment for HIV-infected people and affected families.
Keywords: HIV/ AIDS; Malnutrition; Nutrition